Problems In HOTS Application: A Study of Teacher’s Reflection and Decision Making - Aprilya, Intan Riza; Saifuddin, Muhammad (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2021)
Higher Order Thinking Skill (HOTS) is a demanded strategy to be applied in any teaching activities, including English teaching and learning process. This HOTS application offers attainable learning outcomes to the teachers when conducting teaching activities. Teachers are able to see how far students can learn based on cognitive, affective, and psychomotor aspect. However, there were problems which teachers found and challenged them to encounter the problems to keep the implementation of HOTS successful. This research was carried out to figure out teacher’s self-reflection on problems found and to determine decisions how to encounter them. In line to the research purpose, a qualitative research design was applied within interview and questionnaire. Furthermore, based on teacher’s reflection, it was revealed that during learning activities the students acted unmotivated and lack of confidence; they lacked English interest; and HOTs was not applied properly based on its stages. Then, decision making was established in terms of teaching strategies and lesson planning. In conclusion, despite the importance of creating HOTS to invite students to be creative and critical, problems still remained. Thus, self-reflection did assist teacher to analyze and figure out what teaching weaknesses are and imply to the HOTS application to improve teaching and learning process.